Armed Forces and Society in a Spain in crisis: Security and defence policy of Minister Cospedal (2016-2018) - Navajas Zubeldia, Carlos; Zúñiga Crespo, Javier (Hispania Nova, 2021)
In this article, we will analyse the security and defence policy developed by the Defence Minister, María Dolores de Cospedal, between 2016 and 2018, corresponding to the last two years of the seven-year presidency of the Conservative leader Mariano Rajoy. From a methodological perspective, it should be noted that both authors of the study are specialists in Modern History. Consequently, the methodology specific to this area in general has been applied and, within it, that of so-called Contemporary History in particular. A wide range of sources has been employed throughout the present paper, although secondary sources are rare due to the ground-breaking nature of the analysis. The conclusion, besides emphasising the main findings, also contains a theoretical discussion of the key terms used in our research: Post-militarism and Neo-praetorianism.
Keywords: Armed Forces and society; Spain in crisis; security and defence policy; María Dolores de Cospedal, 2016-2018